2015
DOI: 10.1002/aic.15082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mixing profiles for a new micromixer design strategy

Abstract: The relationship between mixing history and reaction performance in microreactors using computational fluid dynamics (CFD) simulations is identified. In the idealized, simplified mixing model, mixing proceeds linearly and only the mixing time determined the reaction performance. However, in the case of realistic models where mixing proceeds unequally, the partial rapid progression of mixing, more than the mixing time, significantly impacts the reaction. The use of the fluid segment size distribution to capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The mismatch would be caused by the discrepancy between the model considering uniform sized lamellae, and the real fluid dynamics inside the mixer. In fact, the stepwise profile agreed well with our previous computational study on the mixing and reaction with moderate Re in a microchannel with a confluence point 29 . We'd like to note that diffusion in the fully developed laminar flow after the disturbance is slow and hardly achieved within the residence time in the reactor.…”
Section: Determination Of the Dimensionless Numbers Using In-line Measurementsupporting
confidence: 89%
See 1 more Smart Citation
“…The mismatch would be caused by the discrepancy between the model considering uniform sized lamellae, and the real fluid dynamics inside the mixer. In fact, the stepwise profile agreed well with our previous computational study on the mixing and reaction with moderate Re in a microchannel with a confluence point 29 . We'd like to note that diffusion in the fully developed laminar flow after the disturbance is slow and hardly achieved within the residence time in the reactor.…”
Section: Determination Of the Dimensionless Numbers Using In-line Measurementsupporting
confidence: 89%
“…Because of their convenience in evaluating the mixing performance with changing the mixer geometry and operating conditions, many studies on micromixers employed these reaction systems. A linear correlation based on the kinetic model is used to convert the test results to the mixing times. , However, our recent study as well as the discussions on the Villermaux–Dushman reaction system by Kölbl and Kraut proved that the actual mixing time could differ by an order of magnitude from the estimation based on the chemical test reaction systems owing to the complex reaction profiles inside the microreactors. Many studies using computational fluid dynamics (CFD) simulations have revealed important factors for mixer design, though these studies based on CFD simulations are generally focusing on the complex convection phenomena occurring in a specific mixer with a fixed size. An easy-to-use relationship for determining mixing time from the mixer size and operating condition is hardly found to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of simplification is difficult in treating the complex geometrical structure of reactor and the process of coupling multi fields. Recently, with the rapid development of computer science, computational fluid dynamics (CFD) [11][12][13] has been widely applied in studying fluid flow, and regarded as one of the most appropriate approaches used to obtain an intuitive understanding of fundamental phenomena. Especially, in the developed CFD commercial software, solving strategies for the N-S (Navier-Stoke) equations of coupling multi fields and meshing technology for the complex geometry structure have been well developed.…”
Section: Reactor (Pfr) or Continuous Stirring Tank Reactor (Cstr)mentioning
confidence: 99%
“…As part of an inexpensive and simplified approach, zirconia particles, which are widely used as a ceramic material with functional properties such as high mechanical strength, were prepared by neutralization reaction at the interfacial within a tube reactor. Micro reactors are generally applied to gas-liquid or liquid-liquid reactions (Sotowa et al, 2007;Asano et al, 2016). Many kinds of micro-reactors are utilized in various applications.…”
Section: Crystallization In a Tube Reactormentioning
confidence: 99%